Canine mammary tumour cells exposure to sevoflurane: effects on cell proliferation and neuroepithelial transforming gene 1 expression. (May 2019) - Argano, Martina; De Maria, Raffaella; Vogl, Claus; Rodlsberger, Katrin; Buracco, Paolo; Larenza Menzies, M. Paula
Abstract: Objective: The influence of perioperative factors, such as anaesthetic and analgesic techniques, on metastatic spread following surgery for primary cancer removal is of growing interest. The present study investigated the effects of sevoflurane on canine mammary tumour cell proliferation (MTT colorimetric assay) and on the expression of neuroepithelial transforming gene 1 (NET1). Study design: Prospective controlled in vitro trial. Study material: Primary (CIPp) and metastatic canine tubular adenocarcinoma (CIPm) cells. Methods: To perform MTT tests, cell lines were seeded at a density of 3000 cells per well and incubated with sevoflurane (1, 2.5 or 4 mM) or only with the culture medium (control). Sevoflurane was added to the cell cultures every hour to avoid changes in drug concentration. MTT assays were performed after 6 hours of exposure obtaining absolute values of absorbance. The RNA isolated from the lysates of the same cell lines underwent quantitative polymerase chain reaction to evaluate NET1 gene expression changes compared with controls. One- or two-way analysis of variance was used as appropriate ( p < 0.05). Results: A significant increase in cell proliferation compared with controls was observed in CIPp treated with lower sevoflurane concentrations, whereas a significant decrease in cell proliferation was found in CIPm treated with all the sevoflurane concentrations. All CIPp treatments did not induce changes in gene expression compared with controls, whereas a significant increase in gene expression was observed in CIPm between controls and the higher sevoflurane concentration. Conclusions and clinical relevance: Sevoflurane treatments modified the cell proliferation rate in both cell lines showing an increase or decrease when applied to CIPp or CIPm, respectively. Expression of the NET1 gene increased after treatment with sevoflurane 4 mM in metastatic cells. The role of sevoflurane on cancer recurrence should be further investigated.